An Analysis of the views of Muslim Thinkers on the Two Nations Theory- In the context of the formation of Pakistan - Jami, Abd-Ul-Rehman; Al Hassani, Muhammad Nawaz (Al-Irfan, 2021)
It is an accepted and undoubted history of sub-continent that Pakistan has come into being on 1947 on the basis of this perspective that Muslims and Hindus were two different nations. They both had the different ways of life. They had dissimilar political, economic, social, cultural and religious approaches. Their foods, dresses, parties, they ways of celebrations, sports, basic morality, family system, etc. were totally divergent. This standpoint is called “Two Nations Theory”. On the basis of above-mentioned facts, a majority of Muslim leaders demanded a separate homeland where they would spend their lives according to their religion. A number of Muslim leaders had confronted this demand along with Hindus. They thought that their unity would be their strength against the British Empire. But the majority side was vigilant and had been realized that there would be no peace, no contentment and no worldly development for them in united India. So, they turned the public opinion to them under the leadership of Quaid-e-Azam and succeeded in creating Pakistan. After the formation of Pakistan, a third viewpoint was also raised that Pakistan was created on the basis of secularism. Religion has no significant status in modern states. So, the questions have been raised that was the formation of Pakistan on the basis of Two-nation theory or secular Pakistan was the original objective? Is the formation of Islamic nationalism based on religion or race, color, language and geographical boundary? In this article, an effort will be done to see their differences and different views in analytical method.